2022
DOI: 10.1177/00953997211073459
|View full text |Cite
|
Sign up to set email alerts
|

Taking a COVID-19 Vaccine or Not? Do Trust in Government and Trust in Experts Help Us to Understand Vaccination Intention?

Abstract: Governments worldwide are relying on the COVID-19 vaccines as the solution for ending the coronavirus pandemic and the resulting crisis. Although scientific progress in the development of a vaccine has been astonishing, policymakers are facing an extra hurdle as increasingly more people appear to be hesitant in their intention to take such a vaccine. Based on a large Corona survey in Belgium, this study aims to explain the vaccination intention by linking it to trust in government and experts, while accounting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 63 publications
10
32
0
Order By: Relevance
“…From a theoretical point of view, our results seem to confirm that the expected effect of subjective norms, and risk perceptions through fear of COVID-19, is mediated by trust in science. Following literature indications [ 14 , 77 , 79 , 94 , 95 , 96 , 97 ], our results also show the role of trust in science as a key factor, able to modulate both the emotional and social factors responsible for the intention to get vaccinated. Indeed, trust in science consistently emerged as a key determinant of adherence to government indications to avoid the spread of SARS-CoV-2 around the world, as several cross-national studies revealed: this has been found to be the case even regarding the most controversial issue, that is, whether to get vaccinated.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…From a theoretical point of view, our results seem to confirm that the expected effect of subjective norms, and risk perceptions through fear of COVID-19, is mediated by trust in science. Following literature indications [ 14 , 77 , 79 , 94 , 95 , 96 , 97 ], our results also show the role of trust in science as a key factor, able to modulate both the emotional and social factors responsible for the intention to get vaccinated. Indeed, trust in science consistently emerged as a key determinant of adherence to government indications to avoid the spread of SARS-CoV-2 around the world, as several cross-national studies revealed: this has been found to be the case even regarding the most controversial issue, that is, whether to get vaccinated.…”
Section: Discussionsupporting
confidence: 87%
“…The trust in science factor has been transversally recognized as one of the factors capable of explaining different behaviors and attitudes of adherence to health behaviors prescribed in a pandemic situation [77,93]. Following literature indications [14,77,79,[94][95][96][97], trust in science seems to be a key factor, able to modulate both the emotional and social factors responsible for the intention to get vaccinated. Because of this, we formulate the following hypotheses: Hp 5: Trust mediates the relationship between subjective norms and intention to get vaccinated.…”
Section: C Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The contestations about vaccine approval, procurement, and coordinated national plan in Brazil further illustrate the importance of considering politics when responding to pandemics. For instance, trust in government and policy experts is crucial for persuading the public to accept a COVID-19 vaccine ( Wynen et al, 2020 ). In addition, although international guidelines assist in creating a more equitable distribution of vaccines, decisions about uptake are conditioned on agreements made at the production and procurement stage and the marketing authorization norms defined by each country.…”
Section: Discussionmentioning
confidence: 99%
“…Government mistrust is also a leading factor, as this has been reported in multiple studies [31][32][33]. Other factors which have also played in COVID-19 vaccine hesitancy include the effectiveness of the vaccine [3,34], social influence [11], vaccine mandate [35], conspiracy beliefs [3,11], as a small percentage of respondents in this study believed that the COVID-19 had a microchip within it and some believed that it was related to 5G, which could be used to control them.…”
Section: Discussionmentioning
confidence: 52%